Pain and behaviour changes in children following surgery. Issue 10 (17th July 2012) - Power, Nina Mary; Howard, Richard F; Wade, Angie M; Franck, Linda S
Abstract : Objectives: To quantify postoperative pain and problematic behaviour (PB) in children at home following day-case (same day admission and discharge) or inpatient (≥1 night in hospital) surgery, to identify factors associated with PB at 2 and 4 weeks after discharge and to determine whether pain is associated with PB after adjustment for other factors. Patients and methods: Children scheduled for elective surgery were recruited to a descriptive study involving direct observation and self-report questionnaires. The principal outcomes were pain and PB on the 2nd post-discharge day and after the 1st, 2nd and 4th weeks. Results: 131 parents and their children (aged 2–12years) participated in the study. 93% of children had pain and 73% exhibited PB on day 2 after discharge. The incidence of pain and PB decreased over time, but 25% of children still had pain and 32% PB at week 4. Factors associated with PB were child's previous pain experience, parent and child anxiety and parent's level of education. Conclusions: There was a high incidence of pain and PB persisting for several weeks after surgery in this cohort of children. Previous painful medical experiences and anxiety were important modifiable factors that require further attention from healthcare providers and researchers to potentially improve health and social outcomes for children after surgery.